System for Management of Sign on Ship Crew Sealing Books at the Batam KSOP Office at PT. Putra Anambas Shipping Batam - Rolina Berutu; Dirhamsyah Dirhamsyah; Fadiyah Hani Sabila (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
The purpose of this paper is to study how the management process sign on in the ship seaman’s book PT. Putra Anambas Shipping Batam. The process begins with an order from the owner that there will be a crew change, and then proceeds to the KSOP Khusus Batam Office. As for the problem, the problem faced in the sign on crew book process is the late information from the owner to sign on the ship's seaman’s book. As a result, when the ship is to depart, the crew's book has not been signed, which results when the boat is to leave and the sailor's books have not been sign on thus hindering the clereance process. Cooperation and good coordination between the shipping company and the relevant authorities in the sign on book activities of the seafarers is imperative for the smooth handling of crew documents.